Integrating Information Technology in Islamic Education: A Qualitative Study Using Richard Mayer's Multimedia Learning Theory - Muh. Hanif; Mar’atul Qudsiyyah; Naura Dina Syamila Hanifah (AL-ISHLAH: Jurnal Pendidikan, 2025)
Despite extensive research on technology integration in Islamic education, few studies examine its effectiveness through systematic learning theories. A notable gap exists in applying Richard Mayer's Multimedia Learning Theory to Islamic educational contexts. This qualitative study explores the impact of multimedia-based learning on teaching effectiveness in Islamic education. Data were collected from 14 participants, including teachers, students, and school administrators at Purwokerto State Junior High School 2, through in-depth interviews, observations, and document analysis. Thematic analysis was employed to interpret the data. Findings indicate that multimedia tools enhance student engagement and conceptual understanding, consistent with Mayer’s principles. However, implementation is hindered by insufficient infrastructure and limited digital competence among educators. The study highlights that while multimedia learning holds significant potential for improving Islamic education, its success depends on institutional support, technological readiness, and teacher training. To fully leverage multimedia in Islamic education, stakeholders must address infrastructural and pedagogical challenges. Further research is recommended to develop context-specific strategies across diverse Islamic educational settings.